2022
DOI: 10.3390/mi13060884
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of La0.8Sr0.2FeO3-δ-Gd0.2Ce0.8O2-δ Cathode for Solid Oxide Fuel Cells by Surface Modification with BaCO3 Nanoparticles

Abstract: Recently, Fe-based perovskite oxides, such as Ln1-xSrxFeO3-δ (Ln = La, Pr, Nd, Sm, Eu) have been proposed as potential alternative electrode materials for solid oxide fuel cells (SOFCs), due to their good phase stability, electrocatalytic activity, and low cost. This work presents the catalytic effect of BaCO3 nanoparticles modified on a cobalt-free La0.8Sr0.2FeO3-δ-Gd0.2Ce0.8O2-δ (LSF-GDC) composite cathode at an intermediate-temperature (IT)-SOFC. An electrochemical conductivity relaxation investigation (ECR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…BaCO 3 was reported recently to be capable of signicantly reducing the polarization resistance of the electrode. 25,27,29,47 To conrm the function of BaCO 3 in the electrode reaction, calculations of the O 2 molecule adsorption on the surface of the BaCO 3 (100) and SBF(100) were carried out with the models shown in Fig. 3a We use BaCO 3 to inltrate the porous SBF electrode to enhance the electrode reaction kinetics.…”
Section: Electrode Reaction Kinetics Mechanism Of Sbf and Performance...mentioning
confidence: 99%
See 4 more Smart Citations
“…BaCO 3 was reported recently to be capable of signicantly reducing the polarization resistance of the electrode. 25,27,29,47 To conrm the function of BaCO 3 in the electrode reaction, calculations of the O 2 molecule adsorption on the surface of the BaCO 3 (100) and SBF(100) were carried out with the models shown in Fig. 3a We use BaCO 3 to inltrate the porous SBF electrode to enhance the electrode reaction kinetics.…”
Section: Electrode Reaction Kinetics Mechanism Of Sbf and Performance...mentioning
confidence: 99%
“…It is reported that the increase in surface alkalinity could increase surface electron concentration and signicantly enhance the oxygen surface exchange process, thus reducing the polarization resistance. [24][25][26][27][28][29][30] For instance, aer inltrating 9.12 wt% BaCO 3 into La 0.8 Sr 0.2 FeO 3−d -Gd 0.2 Ce 0.8 O 2−d , the R p decreased by 50% at 700 °C compared to the bare sample. 27 Actually, the electrode reaction process consists of several elemental steps, including gas diffusion, oxygen molecule adsorption/dissociation, charge transfer, and oxygen ion migration across the interface between the electrode and electrolyte.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations